Remodeling after acute myocardial infarction: mapping ventricular dilatation using three dimensional CMR image registration - O'Regan,DP; Shi,W; Ariff,B; Baksi,AJ; Durighel,G; Rueckert,D; Cook,SA (Journal of Cardiovascular Magnetic Resonance, 2012)
Background: Progressive heart failure due to remodeling is a major cause of morbidity and mortality followingmyocardial infarction. Conventional clinical imaging measures global volume changes, and currently there is nomeans of assessing regional myocardial dilatation in relation to ischemic burden. Here we use 3D co-registration ofCardiovascular Magnetic Resonance (CMR) images to assess the long-term effects of ischemia-reperfusion injury onleft ventricular structure after acute ST-elevation myocardial infarction (STEMI).Methods: Forty six patients (age range 33–77 years) underwent CMR imaging within 7 days following primarypercutaneous coronary intervention (PPCI) for acute STEMI with follow-up at one year. Functional cine imaging andLate Gadolinium Enhancement (LGE) were segmented and co-registered. Local left ventricular wall dilatation wasassessed by using intensity-based similarities to track the structural changes in the heart between baseline andfollow-up. Results are expressed as means, standard errors and 95% confidence interval (CI) of the difference.Results: Local left ventricular remodeling within infarcted myocardium was greater than in non-infarctedmyocardium (1.6% ± 1.0 vs 0.3% ± 0.9, 95% CI: -2.4% – -0.2%, P = 0.02). One-way ANOVA revealed that transmuralinfarct thickness had a significant effect on the degree of local remodeling at one year (P < 0.0001) with greatestwall dilatation observed when infarct transmurality exceeded 50%. Infarct remodeling was more severe whenmicrovascular obstruction (MVO) was present (3.8% ± 1.3 vs −1.6% ± 1.4, 95% CI: -9.1% – -1.5%, P = 0.007) and whenend-diastolic volume had increased by >20% (4.8% ± 1.4 vs −0.15% ± 1.2, 95% CI: -8.9% – -0.9%, P = 0.017).Conclusions: The severity of ischemic injury has a significant effect on local ventricular wall remodeling with onlymodest dilatation observed within non-ischemic myocardium. Limitatio